TERAPI UAP MINYAK KAYU PUTIH EFEKTIF MENGURANGI SUARA RONKHI PADA PASIENANAK DENGAN ISPA DI RS HERMINA BEKASI - Ela Sri Laela; Ikasa Nandes Yonanda (Institut Kesehatan Hermina, 2024)
Acute respiratory infections (ARI) can attack the nose, throat and lungs. The causes of ARI are bacteria, viruses and fungi. Children are vulnerable to ARI because their immunity is still low. The impact of ISPA if not treated immediately can cause more serious infections, namely lung infections, brain membranes, decreased consciousness, respiratory failure, and can even cause death. One of the appropriate nursing treatments for ISPA cases in children is eucalyptus oil steam therapy. Eucalyptus oil steam therapy is a therapy carried out by inhaling steam that comes from hot water vapor added with eucalyptus oil. The aim of this study was to determine the effect of eucalyptus oil steam therapy in reducing rhonchi sounds in patients at Hermina Bekasi Hospital. The respondents in this study were pediatric patients aged 2 years 8 months. Data from the patient's assessment was coughing up phlegm and crackles were heard in both lung fields. The primary nursing diagnosis is ineffective airway clearance. The nursing action taken was administering eucalyptus oil steam therapy. After administering eucalyptus oil steam therapy 3 x 24 hours with a frequency of 1 time a day for 5-10 minutes using 4-5 drops of eucalyptus oil by covering the head with a clean towel, the patient's ineffective airway cleaning resolved, characterized by coughing and rhonchi sounds in both lung fields. has decreased. Giving wood oil steam therapy is effective in reducing rhonchi sounds. It is hoped that patients and families will be able to apply eucalyptus oil steam therapy at home when their child experiences ARI.